Strengthening The Existence of Waste Village Bank Efforts Through The Establishment of Waste Management Network Development In District District Sukawati Gianyar - Tisnawati, Ni Made; Purbadharmadja, Ida Bagus; Widanta, Anak Agung Bagus; Karmini, Ni Luh (Journal of A Sustainable Global South; Vol 1 No 1 (2017): February 2017, 2020)
Program  waste  bank  has now  become  a national  program  that  must be  implemented in stages  starting from the smallest  unit  of government,  namely  the  village.  Threats  of waste  management  that  are  not  managed  properly,  will  cause environmental problems,  social or economic. The economic potential that could arise from the handling of plastic waste classified mainly re-used and re-cycled actually be enjoyed by bank customers waste. Waste bank system enables to distribute plastic waste classified as re-used and re-cycled to collectors  who paid in accordance  with the market price. But in some other districts in the province  of Bali,  still has  many  obstacles  in the  establishment  and  sustainability.  Even  in  some  villages  in  Gianyar  has not succeeded  in  establishing  the waste  bank  for various reasons.  In  Sub  Sukawati,  there  is  a waste  bank  that  has  a variety  of conditions.  Different  conditions  have to be anticipated  by organizing  networks  between  the movement  of waste banks that are currently conducted  sporadically in District Sukawati.  If implemented fully networked,  it will lead to positive benefits, especially for the waste banks are still not running at maximum.  The initial step to ensuring the sustainability of rural waste bank was started in the conduct Focus Group Discussion held at Banjar Kelod Pagutan Subdistrict Batubulan Sukawati on Thursday, July 14 2016. The result is the information about the existence of waste bank in District Sukawati Gianyar regency, and the formation of group's bank working waste districts throughout Sukawati, Gianyar. K e yw o r d s :   Work Group, Bank of waste, District Sukawati